1993
DOI: 10.1159/000236520
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Lymphocytes FcεRII/CD23 in Allergic Children Undergoing Hyposensitization

Abstract: Owing to the proposed role of FcεRII/CD23 in allergic diseases, we analyzed the expression of this receptor on peripheral blood lymphocytes (pan-B, pan-T and CD4+ or CD8+ T cells) and its autoproteolytic product sCD23 in serum. This was done in 10 asthmatic children allergic to Dermatophagoides pteronyssinus(Dpt) before and 6 weeks after hyposensitization. FACS analysis of double, direct immunofluorescence staining of the whole blood revealed an elevated percentage of FcεRII/CD23+ lymphocytes in allergic child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 25 publications
4
21
0
Order By: Relevance
“…Therefore, enhanced allergen uptake by monocytes and enhanced T cell proliferation might be beneficial in terms of improv ing the efficiency of immunotherapy [37], The change in the expression of CD23 on B lymphocytes during RIT, and its possible correlation with allergen-specific IgE and IgG4, as well as the clinical benefit of immunotherapy has been incompletely investigated. However, a significant decrease in CD20+CD23+ lymphocytes was reported in allergic chil dren after 6 weeks of standard hyposensitization [38]. A similar finding was observed in patients with atopic dermat itis [39], They had an increased number of CD23+ B cells which correlated to the severity of a disease.…”
Section: Discussionsupporting
confidence: 63%
“…Therefore, enhanced allergen uptake by monocytes and enhanced T cell proliferation might be beneficial in terms of improv ing the efficiency of immunotherapy [37], The change in the expression of CD23 on B lymphocytes during RIT, and its possible correlation with allergen-specific IgE and IgG4, as well as the clinical benefit of immunotherapy has been incompletely investigated. However, a significant decrease in CD20+CD23+ lymphocytes was reported in allergic chil dren after 6 weeks of standard hyposensitization [38]. A similar finding was observed in patients with atopic dermat itis [39], They had an increased number of CD23+ B cells which correlated to the severity of a disease.…”
Section: Discussionsupporting
confidence: 63%
“…1c), while CD23® was not found to be significantly elevated. It was already shown using flow cytometry that atopic patients have a higher percentage of Fc²RII/CD23 lymphocytes than healthy controls [25,26]. It may be possible that CD23® is involved in B cell activation and differentiation, while CD23¯could play a role in the T cell-dependent responses to allergens [27].…”
Section: Discussionmentioning
confidence: 98%
“…cDNA was synthesized by using 2.5 g of total RNA isolated from the samples. The cDNA was primed with oligo(dT) [12][13][14][15][16][17][18] and with random hexamer nucleotides (N6) in the absence of signal from the former method. The Fc receptor primers used for PCR were based on the published sequences of the human Fc␥ -RI, -RII, -RIII, and FcRII genes (25,26) and included the following primer sets: Fc␥RI: 5Ј primer, 5Ј-ATGTGGTTCTTGACAAC-TCTGCTC-3Ј and 3Ј primer, 5Ј-ATGTCTGTCTTCTTGAAG-GCTGGA-3Ј; Fc␥RIIA,C: 5Ј primer, 5Ј-GACTCCATTCAGT-GGTTCCA-3Ј; and 3Ј primer: 5Ј-GTCAGCTGTTTCATAGT-CATTG-3Ј; Fc␥RIIB: 5Ј primer, 5Ј-GACTCCATTCAGTGGT-TCCA-3Ј and 3Ј primer, 5Ј-CCCAACTTTGTCAGCCTCATC-3Ј; Fc␥RIII: 5Ј primer, 5Ј-AAGATCTCCCAAAGGCTGTG-3Ј and 3Ј primer, 5Ј-ATGGACTTCTAGCTGCACCG-3Ј; FcRII: 5Ј primer, 5Ј-CGTCTCTCAAGTTTCCAAG-3Ј and 3Ј primer: 5Ј-GCACTTCCGTTGGAATTTG-3Ј.…”
Section: Methodsmentioning
confidence: 99%
“…Accordingly, immune complex͞Fc receptor interactions potentially underlie the progression of the airway inflammatory and bronchoconstrictor responses in asthma, wherein the immediate bronchoconstriction accompanying antigen exposure is followed by the development of the late phase asthmatic response involving various proinflammatory cells. Indeed, recent studies have demonstrated that expression of the inducible form of the low affinity IgE receptor (FcRII or CD23) is up-regulated on monocytes and alveolar macrophages (14), as well as on circulating B lymphocytes (15,16) isolated from atopic asthmatic subjects.…”
mentioning
confidence: 99%